2019
DOI: 10.21815/jde.019.064
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on Growth and Development Curricula for Predoctoral and Advanced Education Orthodontic Programs

Abstract: Dental students and orthodontic residents must demonstrate competence in various areas prior to graduation. However, the Commission on Dental Accreditation (CODA) deinition of competence is broad. The aims of this study were to obtain expert consensus on Growth and Development topics and subtopics in predoctoral and advanced education programs in orthodontics and to determine the level of cognition on the subtopics necessary to demonstrate learner competence. A modiied Delphi method with a consensus threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…1,2 This broad definition presents a challenge to academic programs in identifying the levels of cognition required in predoctoral and advanced education orthodontic curricula for learners to reach competence. 5 Resultantly, didactic content and essential clinical experience vary among programs, and, presumably, so do competencies and outcomes assessment. [5][6][7][8] In 1993, the "Curriculum Guidelines for Orthodontics" 9 (henceforth referred to as 1993 Guidelines) for predoctoral education was published by the American Dental Education Association (ADEA), then known as the American Association of Dental Schools.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 This broad definition presents a challenge to academic programs in identifying the levels of cognition required in predoctoral and advanced education orthodontic curricula for learners to reach competence. 5 Resultantly, didactic content and essential clinical experience vary among programs, and, presumably, so do competencies and outcomes assessment. [5][6][7][8] In 1993, the "Curriculum Guidelines for Orthodontics" 9 (henceforth referred to as 1993 Guidelines) for predoctoral education was published by the American Dental Education Association (ADEA), then known as the American Association of Dental Schools.…”
Section: Introductionmentioning
confidence: 99%
“…5 Resultantly, didactic content and essential clinical experience vary among programs, and, presumably, so do competencies and outcomes assessment. [5][6][7][8] In 1993, the "Curriculum Guidelines for Orthodontics" 9 (henceforth referred to as 1993 Guidelines) for predoctoral education was published by the American Dental Education Association (ADEA), then known as the American Association of Dental Schools. The 1993 Guidelines outlined the predoctoral orthodontic curriculum content in three levels: (level 1) Growth and Development; (level 2) Preclinical Orthodontics; and (level 3) Clinical Experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the comprehensive quality of graduating students in general practice medicine is rare, and evaluation methods suitable for measuring quality do not exist in China and cannot further guide the reform of talent cultivation and reform in general medicine in colleges and universities. In this study, we co-opted the theories and methods of Bloom et al for the measurement of competencies of graduating students in general practice medicine [7]. The competencies were divided into three aspects: knowledge level, working skill and professional accomplishment.…”
Section: Introductionmentioning
confidence: 99%
“…A study has found that an effective FDP increases the participants' motivation 14 through enhancement of knowledge and skills related to the principles of relationship-centred care 15 and well-understood instructional practices in an interactive teaching environment 16 . The Delphi technique is widely used in many sub-disciplines; as well as in assessments, 17 , 18 curriculum development, 19 , 20 and questionnaire development 18 , 21, 22, 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%